Augmenting Science in the Islamic Contemporary World: A Strategic Attempt at Reconstructing the Future - Muqowim Muqowim; Zulkipli Lessy (Al-Jami'ah: Journal of Islamic Studies, 2019)
During five centuries (6th to 11th C.E.), the advancement of science in the Muslim world displayed Muslim civilization as the scientific Mecca. This era saw many other civilizations learning science from Muslims seen as exemplary in modernizing life and sharing guidance for moral conduct. This was accomplished by embedding norms and inventions and as a result of factors such as royal patronage and personal sacrifice. This paper seeks to reclaim historical data through reflection and contextualization. Analysis of relevant past contexts paves a path leading from romanticism and antiquanism into the contemporary world. Secondary resources, such as historical books and journals, reveal how science in Islam was developed and nurtured through patronage, institutional establishment, networking, and other factors, leading to valuable inventions. The Islamic Golden Era of science flourished because Muslims scientists had an ethos motivating them toward discoveries. Key innovating scientists made cities such as Nishapur, Alexandria, Jundishapur, and Damascus become preeminent in scientific invention. This brought rapid development to Muslim life, as well as to the surrounding nations, extending to Greece and India and China. This paper argues that Muslim scientists of today’s world can benefit from the perspective that the Qur’an and hadiths are essential sources of general principles for conducting scientific and technological research. Both are key spirits for encouraging Muslim scientists to conduct rigorous studies.[ Selama 5 abad pertama, 6-11 Masehi, kemajuan ilmu pengetahuan di dunia muslim terwujud pada peradaban muslim di Mekkah. Era ini menunjukkan pelbagai peradaban lain belajar kepada muslim sebagai model kehidupan modern dan petunjuk kehidupan moral. Hal ini teruji oleh norma-norma dan penemuan-penemuan serta hasil akibat dari loyalitas dan keikhlasan. Artikel ini mencoba mengklaim ulang bukti historis melalui refleksi dan kontekstualisasi. Analisa konteks masa lalu yang tepat menghindari dari kecenderungan romantisme dan kekunoan dari pada dunia kontemporer. Sumber sekunder seperti buku dan jurnal, membuktikan bagaimana pengetahuan dalam Islam berkembang dan tumbuh melalui patronase, institusionalisasi, jejaring dan faktor lainnya yang mendukung penemuan baru. Keemasan ilmu masa Islam menjamur karena ilmuwan muslim mempunyai etos yang tinggi pada penjelajahan pengetahuan. Kunci inovasi para ilmuwan telah membuat kota–kota seperti Nishapur, Alexandria, Jundishapur dan Damaskus berkembang menjadi pusat pengetahuan. Perkembangan pesat kehidupan muslim ini akhirnya menyebar ke Yunani, India dan China. Artikel ini menunjukkan bahwa ilmuwan muslim saat ini dapat mengambil manfaat dari perspektif Qur’an dan hadits sebagai sumber utama dalam prinsip-prinsip penelitian ilmiah dan teknologi. Keduanya juga, Qur’an dan hadits, menjadi kunci semangat bagi ilmuwan muslim dalam kajian yang lebih maju.]